Genesi passiva e hyle: la fondazione della coscienza trascendentale - Martelli, Lavinia (Philosophy Kitchen - Rivista di filosofia contemporanea, 2020)
The aim of this paper consists in analyzing the flowing of Husserl’s thought during the genetic analysis and the primordial constitution of transcendental consciousness. The start point is represented by the archaeological, regressive inquiring about perceptual field and the elaboration of passive synthesis as foundational elements to understand the hyletic dimension, the primal time-consciousness and the rise of the unconscious level. The genesis of Abbau, conceived as a dismantling method, allow us to investigate the possibility of experience constitution, critical issue of a keen and correct epistemology. This lead us to the transition from the structure of noetic consciousness to the question about the possibility of experience in itself: how perception is organized in its dynamic relation with the hyletic sphere? How can we get the identical object in the flowing of experience? How is structured, at genetic level, the egological identity? In this exposition I shall study in deep three principal themes of Husserl’s work in the last twenty years: the rising of precategorial dimension (prior to any objectivation), in its being founded in world experience, as possibility of experience itself; the “embodiement” of consciousness in the primal sensibility (passive level) and its grounding on the affective and instinct-driving field (unconscious intentionality); the uncover of unconscious dimension within the conscious sphere and the possibility that unconscious, following Freud’s theory, could be reactivated and could motivate, through sedimentations and associations, the conscious level.